Nutritional strategies used for rapid weigh loss in martial arts athletes during the pre-competition period - Soares, Wellington Danilo (2024)
Introduction and objective: The growing interest in martial arts has resulted in the emergence of new high-level athletes. however, many of these athletes adopt inadequate nutritional strategies, impairing their health and performance. This study investigates the physical symptoms and indicators of pathologies in amateur martial arts athletes who use nutritional strategies for weight loss. Materials and Methods: We carried out a comparative descriptive research with 29 athletes from different fighting modalities, of both sexes. We used an online questionnaire to collect data about the pre- and post-competition routine. Data were analyzed using SPSS version 26.0. Results: Most athletes were satisfied with their overall health, but the use of extreme weight loss strategies affected their personal relationships. The pressure to reach specific weight categories led athletes to adopt restrictive diets and dehydration. Although the majority did not report health problems, a significant portion reported complications. The inappropriate use of pharmacological and hormonal agents was also observed in some cases. Conclusion: The results show the risks associated with the inappropriate use of nutritional strategies for weight loss by amateur martial arts athletes. The lack of professional guidance and dependence on non-specialized sources contribute to the incorrect use of these strategies. This study highlights the importance of attention to nutritional aspects in martial arts, professional guidance and combating the dissemination of false information. Promoting the health and well-being of athletes is key to ensuring healthy and sustainable sporting performance.